Fluid Dynamic Simulation of Sail Design Performance on Sail-Assisted Ship; A Preliminary Study - Ariani, Betty; Ponidi, Ponidi; Coutsar, Ardan Nagra; Sadewa, Reno Adhianta (Universitas Negeri Padang, 2023)
Ships are a reliable means of transportation in an archipelagic country like Indonesia. The high use of fossil fuels in sea transportation is one of the contributors to emissions that needs attention apart from their dwindling availability. Efforts to use sails as an additional propulsion force on ships are one of the green technology issues in shipping for reducing the use of fossil fuels. It is about how the design affects the thrust on the ship. Tests were carried out on models M1, M2, and M3 in variations 0°, 30°, and 45° wind angles in computational fluid dynamic simulation at 12 knots constant speed. Through this article, there will be a discourse related to optimizing the design of the sail to produce energy efficiency and reduce the use of fossil fuels on ships. The shaped M3 makes greater thrust on the ships than the other two models. The tendency of a decrease in the thrust of the sails with an increase in the wind direction angle, the distribution of force in two directions, namely as normal and parallel to the sails, is suspected as the cause.